2018
DOI: 10.1002/jcp.26775
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of Notch signaling with special emphasis on microRNAs: Implications for glioma

Abstract: Glioma is the most aggressive primary brain tumor and is notorious for resistance to chemoradiotherapy. Although its associated mechanisms are still not completely understood, Notch signaling, an evolutionarily conserved pathway, appears to be the key processes involved. Nevertheless, its mechanisms are sophisticated, due to a variety of targets and signal pathways, especially microRNA. MicroRNAs, which are small noncoding regulatory RNA molecules, have been proposed as one of the key mechanisms in glioma path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 127 publications
0
26
0
Order By: Relevance
“…As an important mediator of cancer-related signaling, Notch signaling was an evolutionarily conserved and demonstrated to be associated with glioma. 38 Our data in this study showed that over-expression of Notch1 and Notch2 could promote glioma cell proliferation and migration, which was inhibited by TSNincreased miR-608. Therefore, Notch1 and Notch2 stand out as particular targets for glioma prevention.…”
Section: Discussionmentioning
confidence: 58%
“…As an important mediator of cancer-related signaling, Notch signaling was an evolutionarily conserved and demonstrated to be associated with glioma. 38 Our data in this study showed that over-expression of Notch1 and Notch2 could promote glioma cell proliferation and migration, which was inhibited by TSNincreased miR-608. Therefore, Notch1 and Notch2 stand out as particular targets for glioma prevention.…”
Section: Discussionmentioning
confidence: 58%
“…NOTCH1. 29 hES, 30 Cyclin D1 31 and MMP2 32 were proved to promote Notch signaling pathway activation, while p21, 33 cleaved caspase-3, 34 cleaved PARP 35 and E-cadherin 36 were reported to interdict it. To verify our prediction, the expression of these above proteins that related to Notch signaling pathway, in U138 and U251 cells that after transfection were detected using Western blot.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 , However, differential expression of certain miRNAs might be also involved in pathophysiological mechanisms of GBM recurrence, but there are limited data regarding miRNA expression as GBM progresses (at its recurrence). 7 , 8 , Comprehensive knowledge and understanding of the molecular pathways underlying disease progression, tumor recurrence and response to therapy might be of great importance in future development of more efficient therapies in GBM.…”
Section: Introductionmentioning
confidence: 99%